Implementasi Management Krisis Pariwisata Pada Kebun Raya Eka Karya Bali. - Anggarani, Ni Putu Dewi; Arida, I Nyoman Sukma (JURNAL DESTINASI PARIWISATA, 2018)
Eka Karya Bali Botanical Garden has experienced two times crisis caused by natural factors such as flash floods and landslides. In the last two years there have been recorded two similar natural disasters on Wednesday, December 21 st 2016 and Thursday, February 9 th 2017. This study aims to find out how the effort to implement the management of tourism crisis after natural disasters at Eka Karya Bali Botanical Garden. This research is important because the state of the crisis can happen anytime, and often happens suddenly. In the absence of proper handling, the sustainability of tourism can be threatened. The research methodology used in this research is qualitative research, with in-depth interview technique and literature study . The concepts are used in this research of implementation effort , crisis management and natural disaster to analize the problems . Data are explained by using table and description to explaining the steps that must exist. Moreover, wether Eka Karya Bali Botanical Garden implement tourism crisis management. The results of study show that the flow of the crisis that occurs through four stages, Eka Karya Bali Botanical Garden tends to use traditional management approach, and the results show that Eka Karya Bali Botanical Gardens has not been maximized the implementation of tourism crisis management, especially in the case of natural disasters. Keywords: Implementation, Crisis Management, Natural Disaster, Eka Karya Bali Botanical Garden